Use of DNA technology in forensic dentistry - Ricardo Henrique Alves da Silva; Arsenio Sales-Peres; Rogério Nogueira de Oliveira; Fernando Toledo de Oliveira; Sílvia Helena de Carvalho Sales-Peres (University of São Paulo, 2007)
The established importance of Forensic Dentistry for human identification, mainly when there is little remaining material to perform such identification (e.g., in fires, explosions, decomposing bodies or skeletonized bodies), has led dentists working with forensic investigation to become more familiar with the new molecular biology techniques. The currently available DNA tests have high reliability and are accepted as legal proofs in courts. This article presents a literature review referring to the main studies on Forensic Dentistry that involve the use of DNA for human identification, and makes an overview of the evolution of this technology in the last years, highlighting the importance of molecular biology in forensic sciences.